'Sometimes your safety goes a bit by the wayside' … exploring occupational health and safety (OHS) with student nurses. (September 2016) - Boucaut, Rose; Cusack, Lynette
Abstract: Because nursing is a high risk profession in terms of occupational health and safety (OHS), the topic of OHS is an important component of student nurse education and practice. Seeking ways to enhance curricular content and foster student health, safety and wellbeing is an ongoing pursuit. This pilot study explored nursing student perspectives about OHS in the clinical setting to develop an understanding of student views that could enlighten teaching about this topic within the undergraduate nursing course. Focus groups were held with pre-registration student nurses in two discrete cohort levels (first and third year). Themes were identified from the focus group discussion about trust, knowledge and responsibility. The students demonstrated a sound grasp of clinical hazards and associated administrative controls. Strengthening student awareness of higher order controls and their evaluation would augment their knowledge of legislative requirements. Students may benefit from learning about a risk management approach to OHS which would provide them with a structured basis for problem solving. This may assist them with clinical reasoning about health and safety issues and empower them in aspects of self-care.